The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1590/s0100-67622014000300014
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial das frações granulométricas argila e areia total em um Latossolo Vermelho-Amarelo

Abstract: SPATIAL DISTRIBUTION OF CLAY AND TOTAL SAND SIZE FRACTIONS IN A OXISOL INTRODUÇÃONovas tecnologias utilizadas na área agrária têm facilitado na determinação da variabilidade espacial e temporal de atributos, no seu mapeamento e nas suas correlações, considerando a distância entre as amostras de maneira a representar com maior precisão os fatores que afetam o rendimento das culturas (LIMA et al., 2010). Segundo Corá et al. (2004), os processos e os atributos do solo que determinam o desempenho e a produção das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…It was observed that the spherical model fitted the data series from all the particle-size fractions of the soil, as presented in Table 1. Lima et al (2014) set the particle-size fractions of the soil to the spherical model for the construction of thematic maps by ordinary kriging (Figure 2). Considering the indicative semivariograms, the same pattern of spatial distribution of the occurrence probability is observed between the clay and fine sand fractions, with adjustments to the same model and the same ranges (160 m).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the spherical model fitted the data series from all the particle-size fractions of the soil, as presented in Table 1. Lima et al (2014) set the particle-size fractions of the soil to the spherical model for the construction of thematic maps by ordinary kriging (Figure 2). Considering the indicative semivariograms, the same pattern of spatial distribution of the occurrence probability is observed between the clay and fine sand fractions, with adjustments to the same model and the same ranges (160 m).…”
Section: Resultsmentioning
confidence: 99%
“…The definition of the spatial dependence values allows us to distinguish correlated samples. According to Lima et al (2014), samples that were collected from a distance that is smaller than their range are correlated to each other. That permits the interpolation for spaces that are smaller than the ones adopted in the sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The first assumption was inspired by the fact that, in models with sill, there is similarity between the sample variance and the sample sill (Trangmar, Yost, Uehara, 1985;Lima, G. et al, 2014;Nagahama et al, 2014;Lima, J. et al, 2014;Jordão et al, 2015). So that, it was considered as possible to extend this idea to the power model, turning the sample variance approximately equal to the value of sample equivalent sill, in other words, the sample variance could be considered as the estimate of the equivalent sill.…”
Section: Methodsmentioning
confidence: 99%